PENGARUH EFEKTIVITAS DAN KEPERCAYAAN ATAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA PENGGUNA SISTEM PADA HOTEL–HOTEL BERBINTANG DI YOGYAKARTA - Vincencia Krisiani; A Fenyta Dewi (Modus, 2013)
Tis study aims to provide empirical evidence of the infuence the efectiveness and reliability of the accounting information system on performance users on the system of hotels in Yogyakarta. Te data of this study collected through a survey questionnaire, while the linear regression analysis simple and multiple used to test the data. Variables tested in this study was the efectiveness of information systems accounting as an independent variable, confdence in information systems accounting as an independent variable, and performance of the system as a user dependent variable. Based on the hypothesis test is performed, this study provides evidence. Empirical: (1) the efectiveness of accounting information systems a positive efect on the system users, (2) the trust accounting information system positive efect on the users of the system, (3) efectiveness and confdence over the accounting information.Keywords: accounting information systems efectiveness, confdence in the system accounting information, the performance of system user.